Precision Oncology in Pancreatic Cancer: Experiences and Challenges of the CCCMunichLMU Molecular Tumor Board - Dorman, Klara; Zhang, Danmei; Heinrich, Kathrin; Reeh, Laurens; Weiss, Lena; Haas, Michael; Beyer, Georg; Rössler, Daniel; Goni, Elisabetta; Renz, Bernhard W.; D’Haese, Jan G.; Kunz, Wolfgang G.; et al. (TARGET ONCOL, 2023)
Background: In pancreatic cancer, systemic treatment options in addition to chemotherapy remain scarce, and so far only a small proportion of patients benefit from targeted therapies. Objective: The patients with pancreatic cancer discussed in the CCCMunichLMU Molecular Tumor Board were reviewed to gain a better real-world understanding of the challenges and chances of precision oncology in this hard-to-treat cancer. Methods: Patients with pancreatic cancer who received comprehensive genomic profiling and were discussed in the interdisciplinary Molecular Tumor Board between May 2017 and July 2022 were included. These patients’ medical charts, comprehensive genomic profiling results, and Molecular Tumor Board recommendations were analyzed in this retrospective cohort study. Results: Molecular profiles of 165 patients with pancreatic cancer were discussed in the Molecular Tumor Board. In the 149 cases where comprehensive genomic profiling was successful, KRAS mutations were detected in 87.9%, TP53 in 53.0%, and CDKN2A in 14.1%. 33.3% of KRAS wild-type patients harbored targetable mutations, while these were only found in 19.1% of patients with the KRAS mutation; however, this difference was not statistically significant. 63.8% of patients with successful testing received a targeted treatment recommendation by the Molecular Tumor Board; however, only 3.2% of these were put into practice. Compared to a historic cohort of patients with pancreatic cancer with synchronous metastatic disease diagnosed between 2010 and 2017, the patients from the pancreatic cancer cohort with synchronous metastatic disease had a longer survival. Conclusions: This single-center experience emphasizes the challenges of targeted treatment in pancreatic cancer. Very few patients ultimately received the recommended therapies, highlighting the need for more and better targeted treatment options in pancreatic cancer, early comprehensive genomic profiling to allow sufficient time to put Molecular Tumor Board recommendations into practice, and close cooperation with clinical trial units to give patients access to otherwise not available targeted treatments.
CRIS-Team Scopus Importer:2025-10-13